التفاعل الرمزي بين الشخصيات في رواية "الكرنك" لنجيب محفوظ بالمنظور جورج هيربرت ميد - WAHYUNI, FITRIA ANGGUN (Ma'dubah : Jurnal Bahasa dan Sastra Arab, 2024)
Karnak Café is a novel written by Najib Mahfudz. It was created based on the true story occurred in 1967. This novel is telling about how suffer and chaos of Egypt society was after defeated by Israel. This causes tremendous anxiety and sadness among society. The situation also effects multi perception and symbol from the leader’s interaction. Thus, this novel is appropriate to be studied by using the theory of symbolic interaction by George Herbert Mead's. This research aims to 1) determine the concept of mind in the novel Karnak Cafe. 2) know the concept of self in the novel Karnak Cafe. 3) know the concept of society in the novel Kafe Karnak. The researcher use descriptive qualitative research. The data sources used are novel Karnak Café by Najib Mahfudz, books and journals related to this theory. The data collection technique used was reading and note-taking technique. The technique of data analysis in this study use data reduction, data presentation and drawing conclusions. The results of this research are: (1) on the concept of mind in symbolic interactions in the novel, five data were found which are gestures, symbols, meanings and actions. (2) the concept of self which consists of "I" and "Me", self as "I' was found five data showing the spontaneous nature of characters in the novel, and self as "Me" was found three data of character interactions that follow norms. (3) in the concept of society five data were found which include society, sympathy, conflict and experience.